Proses Re-branding Blishful Indonesia - Aninda Nisya Fitrina; Wulan Tri Gartanti Gartanti (UNISBA Press, 2022)
Abstract. Micro, small and medium enterprises or MSMEs created by the community, especially millennials, are an important pillar in the Indonesian economy. One of them is Blishful Indonesia, a local business in the beauty sector since 2015 which still maintains its home-made products using natural ingredients. Blishful is re-branding in 2021 and requires a strategy from public relations to achieve the goals that have been set. The purpose of this study was to determine the re-branding process carried out by PR Blishful Indonesia through Instagram social media. Using the theory and concept of Public Relations, Public Relations strategy and re-branding process. The method used in this research is a qualitative method with a case study approach. Data collection uses in-depth interviews, observations, and literature studies. The results of this study indicate that the PR strategy used is the strategy of publicity and strategy of persuasion. By using four elements of re-branding, namely repositioning, renaming, redesign and relaunching. Abstrak. Usaha mikro kecil dan menengah atau UMKM yang diciptakan oleh masyarakat khususnya kaum milenial menjadi pilar penting dalam perekonomian Indonesia. Salah satunya adalah Blishful Indonesia merupakan bisnis lokal di bidang kecantikan sejak tahun 2015 yang masih mempertahankan pembuatannya secara home made menggunakan bahan-bahan natural. Blishful melakukan re-brandingpada tahun 2021 dan membutuhkan strategi dari public relations untuk mencapai tujuan yang telah ditetapkan. Tujuan dari penelitian ini adalah untuk mengetahui proses re-branding yang dilakukan oleh PR Blishful Indonesia melalui media sosial Instagram. Menggunakan teori dan konsep Public Relations, strategi Public Relations dan proses re-branding. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Pengumpulan data menggunakan wawancara mendalam, observasi, dan kajian Pustaka. Hasil penelitian ini menunjukan bahwa strategi PR yang dipakai adalah strategy of publicity dan strategy of persuation. Dengan menggunakan empat elemen re-branding yaitu repositioning, renaming, redesign dan relaunching.